2019
DOI: 10.1037/sgd0000335
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation openness and depression symptoms: A population-based study.

Abstract: Background: Compared to heterosexual individuals, sexual minorities (e.g., those identifying as gay, lesbian, or bisexual) are at higher risk of several mental health problems, including suicidality, substance abuse, depression, and anxiety. Research has attributed much of these elevated risks to unique and chronic stress experiences, so-called minority stress, relating to the stigma and prejudice that many sexual minorities face. Less is known about how sexual minority stigma may function as a multilevel soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 237 publications
(596 reference statements)
3
12
0
Order By: Relevance
“…Only two published studies of sexual orientation concealment and mental health problems have used probability-based sampling, in which all residents of the geographic area of study have equal likelihood of being selected into the sample. The results of these studies-that concealment is associated with fewer mental health problems, at least among some sexual minorities (Pachankis, Cochran, & Mays, 2015;van der Star, Pachankis, & Bränström, 2019)-perhaps contradict the assumption drawn across the more common nonrepresentative sampling approaches-that concealment predicts greater mental health problems (e.g., Jackson & Mohr, 2016). Yet studies relying on nonprobability samples overrepresent the experience of sexual minorities who are relatively out and who are otherwise unrepresentative of the general sexual minority population (e.g., consistently younger; Hottes, Bogaert, Rhodes, Brennan, & Gesink, 2016;Kuyper, Fernee, & Keuzenkamp, 2016).…”
Section: The Challenge Of Studying Sexual Minorities Who Concealmentioning
confidence: 82%
See 1 more Smart Citation
“…Only two published studies of sexual orientation concealment and mental health problems have used probability-based sampling, in which all residents of the geographic area of study have equal likelihood of being selected into the sample. The results of these studies-that concealment is associated with fewer mental health problems, at least among some sexual minorities (Pachankis, Cochran, & Mays, 2015;van der Star, Pachankis, & Bränström, 2019)-perhaps contradict the assumption drawn across the more common nonrepresentative sampling approaches-that concealment predicts greater mental health problems (e.g., Jackson & Mohr, 2016). Yet studies relying on nonprobability samples overrepresent the experience of sexual minorities who are relatively out and who are otherwise unrepresentative of the general sexual minority population (e.g., consistently younger; Hottes, Bogaert, Rhodes, Brennan, & Gesink, 2016;Kuyper, Fernee, & Keuzenkamp, 2016).…”
Section: The Challenge Of Studying Sexual Minorities Who Concealmentioning
confidence: 82%
“…Highlighting the importance of probability-based sampling for sexual orientation concealment-related research questions in particular, the two published studies utilizing such sampling find that a sizable proportion (around 10%) of sexual minorities, in both California (Pachankis et al, 2015) and Sweden (van der Star et al, 2019), report completely concealing their sexual orientation from all others. One of these studies found that sexual minority men who have never told another person of their sexual minority status experienced significantly lower odds of major depression than out sexual minority men (Pachankis et al, 2015), whereas the other found that sexual orientation concealment protects against depression for sexual minorities with high social support (van der Star et al, 2019). Population-based studies would likely find that sexual minority individuals living in less-supportive environments are even more likely to conceal their sexual orientation from all others, with potentially distinct pathways to and buffers against mental health problems compared with those living in California and Sweden (Pachankis & Bränström, 2018).…”
Section: The Challenge Of Studying Sexual Minorities Who Concealmentioning
confidence: 99%
“…[30] Also, the proportion of closeted sexual minorities found in low-stigma countries in the EU-LGBT Survey roughly parallels the proportion of this population found in the only two known population-based surveys of the closet, also conducted in low-stigma contexts (i.e., California and Sweden). [31, 32] Another source of estimation imprecision stems from range restriction in our initial predictor. While highly variable, the range of structural stigma across European countries does not cover the upper limit of structural stigma globally; thus, the validity of our extrapolation outside of the range of European structural stigma is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have examined the relationship between outness and depression. Some studies have found that greater outness is associated with lower depressive symptoms (Earle, 2000; Jackson & Mohr, 2016; Kosciw et al, 2012, 2015; Legate et al, 2012; Lehavot & Simoni, 2011; Pachankis, Cochran, et al, 2015; Schrimshaw et al, 2013), whereas other studies have found that greater outness is related to greater depressive symptoms (Pachankis, Cochran, et al, 2015; Pachankis et al, 2020; Riggle et al, 2017; van der Star et al, 2019). Together, these findings suggest that outness may influence mental health through multiple different mechanisms, and that the relationships between outness and mental health may depend on contextual factors.…”
mentioning
confidence: 99%